Development of Problem-Based Learning Model Learning Module To Improve Mathematical Communication and Curiosity of Grade 5 Students - Aunurrokhim Munawir; YL Sukestiyarno M.S.; Sugilar Sugilar (Magistra)
This study aimed to examine the development process, outcomes, and impact of Problem-Based Learning (PBL) modules designed to enhance fifth-grade elementary students’ mathematical communication skills and curiosity in arithmetic. The research was conducted at SDN 2 Cepiring and SDN 5 Cepiring, located in Cepiring District, Kendal Regency, with fifth-grade students as the sample. A development research design was employed, incorporating both qualitative and quantitative analyses. Qualitative data were analyzed through validation assessments of the module, syllabus, and lesson plans, while quantitative data were analyzed using t-tests and simple linear regression. The validation results from expert reviewers indicated that the module, syllabus, and lesson plans each received an average score of 3.812, equivalent to 95.3%, which falls under the "Very Good" or "Very Feasible" category. The module’s effectiveness was further supported by post-test results, where the control group achieved an average score of 66.11, while the experimental group attained a higher average of 79.85. The t-test analysis yielded a t-value of 5.501 with a significance level of 0.000, indicating a statistically significant difference (p < 0.05) and confirming the module’s effectiveness in improving students’ mathematical communication and curiosity. Additionally, the N-Gain analysis revealed a modest improvement of 17.83% in the control group (from a pre-test average of 59.07 to a post-test average of 66.37), compared to a substantial gain of 60.40% in the experimental group (from 58.23 to 75.23). These findings affirm that the developed PBL module is effective in enhancing students’ learning outcomes in mathematics.